Altitude training of Kenyan top-class marathon runners - Iaia, M.; La Torre, A. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
During the past two decades Kenyan runners have dominated the international middle- and long-distance running scene. Most of the Kenyans who are such good runners come from a group of small tribes called Kalenjin, among which the Nandis are the best performers. These athletes live and train at an altitude of around 2000m above sea level, but most of the major competitive events are held at sea level (Larsen, 2003) Based on the physiological pattern of a marathon race, it is clear that the training of elite runners should focus on improving runners` ability to sustain exercise at the highest intensity over a very long period of time. This is achieved by performing moderate and high-intensity aerobic training in a regular manner. (Billat, 2001). In a typical week for top-class runners during the preparation period before an international marathon, the athletes each run a weekly total distance of around 200 kilometres and have thirteen training sessions in seven days, i.e. one session of short-interval training at an intermediate speed between their velocity over 1,500 and 10,000m (20 x 400m in 60 -65 sec with active pauses of 45s-1min or 8-12 x 1,000m in 2min 50sec with 2min of rest), one session of longinterval training at about vhalf-marathon (5-6 x 2,000m or 3,000m at ~20-21km/h with 2-min rests or active pauses of 1,000m run in 3min 30sec), with the remainder being low-moderate intensity runs (~ 1h each training session), keeping the afternoon after the long-distance run (32-38km in approximately 1h50 min -2h20 min) free. However there are great variations depending on the physical status of the athlete and the coach`s experience. To obtain information about athletes` training loads, the running speed can be controlled and heart rate plus blood lactate determinations may be used. It should however be emphasised that such measurements do not provide a completely clear picture about anaerobic energy production during training, although it should be pointed out that the contribution from the anaerobic system is probably small during this type of exercising. Experience shows that during high-intensity aerobic training sessions, the strongest runners are able to maintain almost the same exercise intensity they perform at sea level (e.g. heart rate between 88-92% HR max, blood lactate ranging from 4 to 9mmol/l for run repetitions over 1,000m), while the running speed is slightly lower (~ 6-10sec per km) during specific middle- or long-distance runs. From a practical point of view there has been growing interest regarding the best time to compete at sea level following a period of training at altitude. But so far there is no scientific evidence to suggest an optimum time as recently demonstrated by two top-class runners who competed at 2 and 21 days after returning to sea level, producing their best marathon performances in 2h 08min and 2h 0 7min respectively. Further research is needed to better evaluate the optimum time between the end of altitude training and race day.